Micronutrient enrichment mediated by plant-microbe interactions and rice cultivation practices. (28th July 2016) - Adak, Anurup; Prasanna, Radha; Babu, Santosh; Bidyarani, Ngangom; Verma, Shikha; Pal, Madan; Shivay, Yashbir Singh; Nain, Lata
ABSTRACT: A field experiment was conducted to evaluate the effect of different plant growth promoting microorganisms (PGPM) on micronutrient enrichment of rice crops grown under conventional (flooded) and SRI (System of Rice Intensification) practices. Significant differences were recorded among treatments and cultivation practices in terms of soil microbial activity reflected in enhanced nutrient uptake, enzyme activity, and yield. The Anabaena -based biofilm inoculants were particularly superior under both methods of cultivation, leading to 13–46% enhancement of iron and 15-41% enhancement of zinc in rice grains over uninoculated controls. SRI was found to be superior in terms of enhancing the concentration of zinc, copper, iron, and manganese (Zn, Cu, Fe and Mn), particularly in grains, and significant in increasing the activity of defense- and pathogenesis- related enzymes and yield parameters. This study illustrates the utility of cyanobacteria-based inoculants for both methods of rice cultivation and their significant interactions with the plant, leading to micronutrient enrichment of rice grains. Such formulations can complement the current biofortification strategies and help in combating the problems of malnutrition globally.